2016
DOI: 10.1071/aj15026
|View full text |Cite
|
Sign up to set email alerts
|

The use of stable carbon isotope trends as a correlation tool: an example from the Surat Basin, Australia

Abstract: The Surat Basin’s Middle Jurassic Walloon Subgroup is a productive coal seam gas source in Queensland, Australia. The Walloon Subgroup can be subdivided into the Upper and Lower Juandah coal measures, the Tangalooma Sandstone, the Taroom Coal Measures, and the Eurombah/Durabilla Formation, from top to bottom. Correlation across the basin is challenging due to high lateral variability and lack of extensive stratigraphic markers. The Walloon Subgroup is also, in places, incised by the overlying Springbok Sandsto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Maximum depositional ages were determined by applying the 'youngest 1σ grain cluster' method of Dickinson & Gehrels (2009), as this style of age determination provided the best match to the CA-TIMS ages of the tuffs of the Walloon Subgroup (Table 5- Chinchilla 4 was adjusted based on stable carbon isotopic trends in coal (as outlined in Hentschel et al (2016b). BSS=basal Springbok Sandstone, UJCM=Upper Juandah Coal Measures, LJCM=Lower Juandah Coal Measures, TSS=Tangalooma Sandstone, UTCM=upper Taroom Coal Measures, LTCM=lower Taroom Coal Measures. with the Walloon Subgroup (Adams et al, 2007).…”
Section: 71! Maximum Depositional Ages and Their Implications For mentioning
confidence: 99%
See 4 more Smart Citations
“…Maximum depositional ages were determined by applying the 'youngest 1σ grain cluster' method of Dickinson & Gehrels (2009), as this style of age determination provided the best match to the CA-TIMS ages of the tuffs of the Walloon Subgroup (Table 5- Chinchilla 4 was adjusted based on stable carbon isotopic trends in coal (as outlined in Hentschel et al (2016b). BSS=basal Springbok Sandstone, UJCM=Upper Juandah Coal Measures, LJCM=Lower Juandah Coal Measures, TSS=Tangalooma Sandstone, UTCM=upper Taroom Coal Measures, LTCM=lower Taroom Coal Measures. with the Walloon Subgroup (Adams et al, 2007).…”
Section: 71! Maximum Depositional Ages and Their Implications For mentioning
confidence: 99%
“…Previous work also showed that the coal measures of the Walloon Subgroup and their clastic interburdens show a high degree of lateral variation in their lithology and continuity. Regional isotope excursion detected in the coals as a correlation tool (Hentschel et al, 2016b). Depositional ages interpreted from U-Pb detrital zircon geochronology show that the 'upper coal measures' on the Roma Shelf are significantly younger than their eastern equivalents, and that these are better correlated with the coals of the overlying Springbok Sandstone (Hentschel et al, 2017).…”
Section: 2! Introductionmentioning
confidence: 99%
See 3 more Smart Citations